PENGARUH BAHAN AJAR INTERAKTIF TERHADAP HASIL BELAJAR SEJARAH SISWA SMA DI PADANG PANJANG : APLIKASI COURSE LAB 2.4 - Yosi Oktaviana; Wahidul Basri; Aisiah Aisiah (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2019)
This study aims to look at the effect of using interactive course lab teaching materials on students' ability to understand concepts in historysubject. The problem of this study is the low level of students' knowledge of the concept material which is indicated by the low learning outcomes of IPS X grade students of high school in Padang Panjang are still many under the KKM (75). The teacher still does not use interactive teaching materials in learning. For this reason, we need an interactive teaching material that has not been used in Padang Panjang High School which is expected to improve learning outcomes. In connection with that Alvani Maizal Asri (2018) has made an interactive teaching material in his research entitled